In vivo systemic toxicity assessment of an oxidized dextrin-based hydrogel and its effectiveness as a carrier and stabilizer of granular synthetic bone substitutes - Pereira, Isabel (2019)
The worldwide incidence of bone disorders is raising, mainly due to ageing population. The lack of effective treatments is pushing the development of synthetic bone substitutes (SBSs). Most ceramic-based SBSs commercially available display limited handling properties. Attempting to solve these issues and achieve wider acceptance by the clinicians, granular ceramics have been associated with hydrogels to produce injectable/moldable SBSs. Dextrin, a low-molecular-weight carbohydrate, was used to develop a fully resorbable and injectable hydrogel. It was firstly oxidized with sodium periodate and then cross-linked with adipic acid dihydrazide. The in vivo biocompatibility and safety of the dextrin-based hydrogel (HG) was assessed by subacute systemic toxicity and skin sensitization tests, using rodent models. The results showed that the HG did not induce any systemic toxic effect, skin reaction or genotoxicity, neither impaired the bone repair/regeneration process. Then, the HG was successfully combined with granular bone substitute, registered as Bonelike® (250-500 ?m) to obtain a mouldable/injectable SBS, which was implanted in tibial fractures in goats for 3 and 6 weeks. The obtained results showed that HG allowed the stabilization of the granules into the defect, ensuring effective handling and moulding properties of the formulation, as well as an efficient cohesion of the granules. This article is protected by copyright. All rights reserved.